Mingling and mixing features in basaltic Andesites of the Eastern Cordillera (Central Andes, 24°s): a petrographic and microanalytical study - Gioncada, Anna (2006)
The basaltic andesites of the Diego de Almagro volcanic complex (Central Andes, 24°S, 66°W) were erupted during Late Miocene at 300 km from the active arc, in the Eastern Cordillera, at the easternmost end of an important strike-slip structure, the Calama-Olocapato-El Toro. These volcanic rocks preserved traces of their pristine history in the form of xenocrysts and in the diverse populations of phenocrysts coexisting due to magma mixing. In Central Andes, crustal contamination commonly conditions the composition of magmas ascending through the thick continental crust, masking the characteristics of the mantle sources. Thus, we carried out detailed petrography and mineral chemistry studies on selected Diego de Almagro basaltic andesites, with the aim to identify the populations of crystals in equilibrium with mafic melts. The results suggested that mixing of basaltic and andesitic magmas occurred during the ascent and storage in the crust. The fraction of basaltic magma prevailed in the mixing process compared to the andesitic one. Crystal zoning and disequilibrium features indicate that magma mixing produced intimate hybridisation. The preservation of primitive crystal assemblages is probably due to the geological situation in which the Diego de Almagro complex emplaced, that favoured the formation of monogenetic volcanic centres rather than of a central volcanic edifice, thus limiting the residence of mafic magmas in the crust and their interaction with crustal partial melts.